Experiences of adults who as children lived with a parent experiencing mental illness in a small-scale society:A Qualitative study - Dam, Kristianna; Joensen, Durita G; Hall, Elisabeth (Journal of Psychiatric and Mental Health Nursing, 2018)
What is known on the subject?: Children of parent with severe mental illness are often carrying a caring burden; they keep the illness in the family, are documented to be stigmatized, bullied and to take special attention to their mentally ill parent's health and well-being. Little is however known about these children's experiences when growing up in a small-scale society. What this study adds to existing knowledge?: Children's experiences of living with a parent with severe mental illness in the small-scale society (Faroe Islands) are paradoxical, life is often unreasonable and evidently contradictory but anyway connected. The results show that “everybody knows everybody” which refers to that, in the small-scale society, it is difficult to be anonymous. The children were familiar with that people talked and had a prejudiced attitude; this resulted that the participants were constantly reminded of their mental ill parent's difference, and they were feeling less worthy than their pals. Children of parents with severe mental illness in a small-scale society need to support from the close family as well as mental healthcare professionals. What are the implications for practice?: The study adds knowledge about the challenges that children of mental ill parents have to go through. Dialogue among mental healthcare colleagues not only about caring for the sick parent but also about modes of caring for the children and the family at large would deepen the staff's knowing of the need for family-centred care within mental health care. Abstract: Introduction An estimated 23% of children worldwide live with a parent experiencing mental illness. These children are exposed to emotional and psychosocial challenges. Little is known about these children when living in small-scale societies. Aim To explore how adults, who as children lived with parents experiencing mental illness in a small-scale society, recalled their childhood life. Method Individual interviews with 11 adults were analysed using content analysis. Results ...